Usage of «level of insecurity risk» indicator as criterion of decision making in department of enterprise economic security - Ілляшенко, Олена Вікторівна (Technology audit and production reserves, 2016)
System support of economic security is possible only in case of existence of economic security system at the enterprise. Form of objectification of such system is subdivision of enterprise economic security (department or division). Criteria of decision making in providing security for enterprise activity are important instruments among others instruments of department of enterprise economic security. One of such criteria is indicator «insecurity level». Its content is shown using antonymous notions «security» and «insecurity». Indicator «level of insecurity risk» should be calculated not only for objects of enterprise economic security system but in the process of making important managerial decisions by top management and owners of enterprise concerning enterprise activity. Applying method of profiling is considered to use suggested indicator «level of insecurity risk» in providing enterprise economic security. Methods of fuzzy logic are suggested to calculate value of insecurity risk levels. Algorithm of insecurity risk evaluation is shown using making profile of insecurity risk for supplier of material goods.